2013
DOI: 10.1038/srep02395
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Strategy to Boost the Quantum Yield of Luminescence of Europium Complexes

Abstract: Lanthanide luminescence has many important applications in anion sensing, protein recognition, nanosized phosphorescent devices, optoelectronic devices, immunoassays, etc. Luminescent europium complexes, in particular, act as light conversion molecular devices by absorbing ultraviolet (UV) light and by emitting light in the red visible spectral region. The quantum yield of luminescence is defined as the ratio of the number of photons emitted over the number of UV photons absorbed. The higher the quantum yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 19 publications
4
64
0
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21] Lanthanide complexes with asymmetric coordination structures exhibit high emission quantum yields (Φff) and large radiative rate constants (kr). [22,23] Lanthanide complexes generally provide eightcoordinate square anti-prism structures that are categorized as D4d in point group theory (8-SAP, Figure 1a). Recently, Hasegawa and co-workers have synthesized more asymmetric lanthanide complexes with eight-coordinate trigonal dodecahedron (8-TDH: D2d, Figure 1b) and nine-coordinate monocapped square anti-prism (9-SAP: C4v, Figure 1c) structures.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Lanthanide complexes with asymmetric coordination structures exhibit high emission quantum yields (Φff) and large radiative rate constants (kr). [22,23] Lanthanide complexes generally provide eightcoordinate square anti-prism structures that are categorized as D4d in point group theory (8-SAP, Figure 1a). Recently, Hasegawa and co-workers have synthesized more asymmetric lanthanide complexes with eight-coordinate trigonal dodecahedron (8-TDH: D2d, Figure 1b) and nine-coordinate monocapped square anti-prism (9-SAP: C4v, Figure 1c) structures.…”
Section: Introductionmentioning
confidence: 99%
“…The radiative rate constants k r observed for lanthanide complexes greatly depend on the geometrical symmetry of the coordination structure. Lima et al has demonstrated that the distortion of coordination geometry of lanthanide ion leads to high emission quantum yields [7]. We have also reported that the asymmetric dodecahedron structure give rise to high k r [9].…”
Section: Introductionmentioning
confidence: 73%
“…In order to maximize the luminescence efficiency of lanthanide complexes, two considerable approaches are commonly accepted [7,8]. The one is suppressing nonradiative rate constant k nr and the other is enhancing radiative rate constant k r .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Luminescent europium complexes act as light conversion molecular devices, and offer an attractive substituent for the commonly used organic fluorophores due to their photochemical stability, long luminescence lifetimes and sharp emission peaks. 4 The Laporte-forbidden transitions of europium causing weak excitation of electrons are overcome by using a sensitizing chromophore or antenna as a ligand in the complex. 4 Various N-heterocyclic ligands including pyridine, phenanthroline, benzimidazole, pyrazole, oxazoline, hydroxylquinoline, azaxanthone, etc., have been employed as efficient sensitizing chromophores for the photoluminescence of europium; in particular, aromatic pyridine ligands are good candidates for enhancing the luminescence properties of Eu and other lanthanides due to their strong binding abilities to the lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%
“…4 The Laporte-forbidden transitions of europium causing weak excitation of electrons are overcome by using a sensitizing chromophore or antenna as a ligand in the complex. 4 Various N-heterocyclic ligands including pyridine, phenanthroline, benzimidazole, pyrazole, oxazoline, hydroxylquinoline, azaxanthone, etc., have been employed as efficient sensitizing chromophores for the photoluminescence of europium; in particular, aromatic pyridine ligands are good candidates for enhancing the luminescence properties of Eu and other lanthanides due to their strong binding abilities to the lanthanide ions. 5,6 The pyridine chromophores incorporated in chelate ligands such as beta-diketonates or carboxylate ligands are known to afford highly stable complexes which prevent the non-radiative decay.…”
Section: Introductionmentioning
confidence: 99%